(3QSGdI aj CSe GdaGYds - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg hHYO aEfc SCdJ Yf GSe GdaGYd gd gh MbjbI ai GdMGd eLGR ai GdeGVi hGdESJbHGd s
(3BNQgG (B:s
(3adjS GdeQGO HMGOKI eYfi GdMOhK GdMbjbi hgh GdhLhO HYO GdYOe , Hd GdeQGO HMGOKI eJLOOI bGd eDdag hcJH YGe (B1278 s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs